Modified sports training and its relationship to the level of academic achievement among hearing-impaired children. - Cherifi, halim (sports creativity, 2024)
Both (modified sports training and academic achievement) are considered important aspects for children with hearing disabilities, as we find that children with hearing disabilities are vulnerable to several psychological problems and behavioral disorders, resulting from their feelings of inferiority, marginalization, and fear of the future, and for this reason, special programs have been developed to take care of these people to integrate them. Correctly in society and playing roles According to many specialized studies, the effectiveness of modified sports training has been proven on many social, psychological, and health aspects for this group. Therefore, through our research, we wanted to highlight the relationship and determine its type between the modified sports training variable and the level of academic achievement of children with hearing disabilities.